ENVIRONMENTAL CRISIS IN RAJA AMPAT CONSERVATION AREA: A GEOSPATIAL STUDY AND ENVIRONMENTAL ETHICS PERSPECTIVE - Inriyatni Sri Pertiwi Ginting; Febriyanti Angelia Ginting (Geographica: Science and Education Journal, 2025)
The Raja Ampat conservation area in Southwest Papua is facing increasing ecological pressure due to nickel mining activities taking place on small islands such as Gag, Kawei and Manuran. This study aims to analyze the environmental crisis through a literature review approach with a geospatial and environmental ethics perspective. The results show significant changes in land cover between 2015 and 2023, characterized by secondary forest degradation and increased marine sedimentation around the mine site. Spatial data from various sources indicate overlaps between mining business licenses (IUPs) and conservation zones, potentially weakening the ecological function and integrity of conservation areas. In terms of environmental ethics, the practice of resource exploitation in this high ecological value area reflects an anthropocentric approach that ignores the intrinsic value of nature and the rights of local communities to a sustainable living space. This study recommends the need for a moratorium on mining in conservation areas, synchronization of spatial planning policies, strengthening the participation of indigenous peoples, and integrating the principles of ecological justice in environmental decision-making.